2023
DOI: 10.3390/su151813743
|View full text |Cite
|
Sign up to set email alerts
|

AI Chatbot Adoption in SMEs for Sustainable Manufacturing Supply Chain Performance: A Mediational Research in an Emerging Country

Rashmi Ranjan Panigrahi,
Avinash K. Shrivastava,
Karishma M. Qureshi
et al.

Abstract: AI chatbots (AICs) have the potential to increase the sustainability of a manufacturing supply chain (SC) through sales engagement and customer engagement to accomplish various activities related to logistics and SC in real time. Industry 4.0 (I4.0) has opened up several opportunities with internet-based technologies, along with challenges for small and medium enterprises (SMEs). SMEs are beginning to adopt such technologies for their competitive advantages and the required sustainability in the manufacturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The PLS-SEM analysis found that economic sustainability practices embedded in the supply chain, such as investments in AI, IoT technologies, value creation for stakeholders, product innovation and design, and ensuring transparency and accessibility of financial and economic information, lead to improved business performance. Similar business practices related to sustainable sourcing, green design, and integrating AI tools for creating circular supply chains that close the loop and improve business performance have been the subject of previous studies [115][116][117]. At the same time, environmental sustainability contributes to business performance through optimizing material resource efficiency, efficient waste management, use of environmentally friendly product packaging, efficient water and energy management, and reduction in carbon emissions from supply chain activities.…”
Section: Implications For Researchmentioning
confidence: 91%
“…The PLS-SEM analysis found that economic sustainability practices embedded in the supply chain, such as investments in AI, IoT technologies, value creation for stakeholders, product innovation and design, and ensuring transparency and accessibility of financial and economic information, lead to improved business performance. Similar business practices related to sustainable sourcing, green design, and integrating AI tools for creating circular supply chains that close the loop and improve business performance have been the subject of previous studies [115][116][117]. At the same time, environmental sustainability contributes to business performance through optimizing material resource efficiency, efficient waste management, use of environmentally friendly product packaging, efficient water and energy management, and reduction in carbon emissions from supply chain activities.…”
Section: Implications For Researchmentioning
confidence: 91%
“…Consequently, big data analytics have been reported to enhance performance positively [ 106 ]. In parallel [ 8 ], found that AI Chatbots improve SMEs' sustainable supply chain performance. It was reported that employing AI can enhance firms' performance by reducing lead times, revolutionizing customer service standards, and delivering personalized experiences [ 107 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this standpoint, firms are introducing AI technologies to establish a CA system that can quickly respond to an ever-changing business environment. Through such technologies, firms can improve problem-solving abilities, boost productivity and efficiency in customer service and other fields [ 2 ], and improve their performance and productivity [ [3] , [4] , [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…In the dialogue with users, the chatbot presents information on habits and practices that people can adopt to behave responsibly and correctly. Situations like "So YES" and "So NO" are also exemplified to increase the impact and encourage people to adopt a circular lifestyle daily [46,47].…”
Section: Information On Sustainable Practicesmentioning
confidence: 99%